ANAK PUTUS SEKOLAH PADA SUKU AKIT DI DESA TANJUNG KEDABU KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Novia Putri; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in Tanjung Kedabu Village, Rangsang Pesisir Sub-District, Meranti Archipelago District. It addresses to the parents of drop-out children and the children themselves in Akit tribe. The aim was to find out the cause of school dropouts and the views of parents towards Akit children who dropped out of school in Tanjung Kedabu Village. This research is a survey research using descriptive qualitative methods, data collection by means of interviews, observation, and documentation. The number of informants in this study was 10 people consisting of 4 parents of the Akit tribe whose children were dropped-out of school, 4 children of the Akit tribe who had dropped out of school, the headman of Tanjung Kedabu village and teacher in the village of Tanjung Kedabu. The results showed that the causes of school dropouts were divided into two, namely internal causes such as low interest and willingness of children to go to school, schools were considered unattractive and inability to take lessons while external causes were family economy, parental attention and playing environment. The views of parents of Akit tribes in the village of Tanjung Kedabu towards the dropped-out students can be seen from several views, namely the knowledge, needs, pleasure or hobbies of a person and habits or patterns of daily life. Keywords: School Dropouts, Causes, Views